Interrelation of the concepts «legal influence» and «administrative-legal influence» - Голуб, Віктор Олександрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The author analyzes the concept of «legal influence» and «administrative-legal influence» and examines their interrelation. Also the scientific positions related to understanding the essence of these concepts are analyzed. The author gives characteristic of the features, structural elements and forms of the administrative-legal influence.